Poverty and Academic Performance of primary Schools in Kabale Municipality. - Justus, Niwagaba (Kabale University, 2020)
The study was on the effect of poverty on academic performance in municipality schools of Kabale district. The study was carried out under three objectives; to find out how the home environment of the child affect his/her academic performance; to establish how poor feeding of the child affects his/her performance and how inadequate scholastic materials affect the pupils’ academic performance. The study was conducted using both qualitative and quantitative approaches. The sample size of the study included; 1 inspector of schools, 5 head teachers, 36 teachers, 8 PTA members and 40 pupils. The sample study was selected using purposive and simple random sampling techniques and data was collected using observation check list, interviews and questionnaires. Data was described, presented using tables and analyzed using percentages in drawing conclusions and recommendations. The findings indicated that the home environment of the child had a direct bearing on his/ her academic performance. Families with conducive and flexible learning environments provided the pupils with reading and writing skills which were benchmarks for good performances. The study also found out that the educational level of the parents, number of members in the family and the parent’s marital status attributed to the child’s behavior, attitude towards education and academic performance. On feeding of pupils, the study found out that every pupil deserved good feeding at school and at home. Therefore the quality, quantity of food served, when and how much is served had a direct bearing on the pupil’s performance in all the schools. On inadequate scholastic materials, the study found out that most schools lacked the basic teaching and learning materials like text books, classrooms, desks, libraries, offices and good toilets, notebooks, pens, mathematical tools, maps, Graphs and other curricula copies in almost all the schools. The study concluded that the absence of scholastic materials affected the over- all performance in schools. On home environment, the study recommended for more sensitization on the parents through work- shops, seminars and meetings on the relevant conditions or the provision of flexible environment both at school and at home. On feeding of pupils, the study recommended for the feeding of children on a well -balanced diet. The quality and quantity of foods taken by the child have a direct bearing on academic performance. The study also recommended for the provision of adequate scholastic materials like uniforms, text books, pens, pencils, mathematical sets, maps, graphs, charts, libraries and good structures. Their adequacy had a direct bearing on the pupils’ academic performance.